Systematic Review and Meta-Analysis: Risk of Post-ERCP Cholangitis with Air or CO2 versus Contrast Cholangiography in Perihilar Malignant Biliary Obstruction - Giri, Suprabhat; Harindranath, Sidharth; Anirvan, Prajna; Kumar, Lohith; Sundaram, Sridhar (Journal of Gastrointestinal Infections, 2023)
Background Endoscopic retrograde cholangiopancreatography (ERCP) may be associated with a risk of postprocedural cholangitis in case of failed drainage of the injected contrast. The present meta-analysis was conducted to assess whether air cholangiography reduces the risk of post-ERCP cholangitis compared with contrast injection.Methods A comprehensive search of MEDLINE, EMBASE, and Science Direct from inception to September 2022 was done for studies comparing air or CO2 and contrast agent for cholangiography during ERCP, with the last search on September 31, 2022. Dichotomous outcomes were analyzed using risk ratios (RRs) with 95% confidence intervals (CIs).Results A total of seven studies were included in the final analysis. Among these, there were three randomized trials and four retrospective studies. The included studies had moderate to high risk of bias. There was no difference in the clinical success rate (RR: 1.02, 95% CI: 0.94–1.09; I2 = 0%), but a lower risk of all-cause adverse events (AEs) (RR: 0.21, 95% CI: 0.12–0.36; I2 = 0%) with air cholangiography, compared with contrast cholangiography. Concerning individual AEs, this difference was seen only for cholangitis (RR: 0.51, 95% CI: 0.37–0.69; I2 = 0%) but not for post-ERCP pancreatitis, perforation, and bleeding. Reintervention and 30-day mortality remained comparable between groups. The certainty of evidence remained low to very low.Conclusion Air or CO2 cholangiography reduces the risk of overall AE, especially post-ERCP cholangitis, compared with contrast cholangiography. Further trials are required to validate the findings of the study.
Keywords: ERCP; cholangitis; air cholangiography; Klatskin tumor; meta-analysis